TELEGRAM AS A MULTIFACETED PLATFORM FOR ANTI-MAINSTREAM POLITICAL PASSION: THE FINNISH FRINGE GROUPS UNDER THE SCOPE - Tuomola, Salla; Kristensen, Jakob Bæk (AoIR Selected Papers of Internet Research, 2026)
This study examines the ecosystem of anti-mainstream groups on Telegram, with a particular focus on Finnish actors within the right-wing and anti-systemic frameworks. Drawing on Mouffe’s (2005a) concept of political passion, we investigated how anti-mainstream attitudes manifest on this fringe platform, which facilitates open, uncensored, and anonymous political discourse, involving radicalised and extremist actors. Using Finnish Telegram groups as a case study, we conducted a network analysis to map the landscape, identifying four distinct clusters of actors and analysing the similarities and differences in their information-sharing practices. We then applied thematic analysis to uncover the key characteristics of these clusters, highlighting how information can flow from fringe actors to influence more prominent accounts. Unlike other studies on Telegram, our analysis did not find significant far-right activity. However, it revealed how marginalised voices can swiftly evolve from general critiques to extreme viewpoints, often fuelled by conspiracy theories and Russian propaganda. We demonstrated how anti-mainstream voices within the fringe platform can merge with radicalised content, deliberate disinformation, conspiratorial messages, and harmful information operations. Specifically, we highlight how Mouffe’s (2005) initial concept of political passion can operate in a digital environment in which information flows between suppliers and distributors. The more passionately a supplier engages—both in volume and tone of their posts—the more attention they attract across all the clusters. In this way, passion functions as a form of currency within the attention economy (c.f., Heitmayer, 2025), ensuring that suppliers garner enough attention to effectively convey their message.